Uso de Beauveria bassiana (Bals.) Vuill. no controle do Tetranychus urticae na cultura do morangueiro - Bin, Mateus (My University, 2021)
The aim of this study was to evaluate the use of Beauveria bassiana to control the spotted spider mite. The experiment was carried out at the University of Caxias do Sul. The treatments consisted of: Water (T1), Ballvéria® (Beauveria bassiana) at a dose of 1 kg/ha (T2), Ortus® (active ingredient: fenpiroximate), at the dose 500 ml/ha and Oberon® (active ingredient: spiromesifen), at a dose of 500 mL∙ha-1 (T3). Three strawberry leaf discs were inserted into Petri dishes, where they already contained moistened filter paper. Eight adult mites were placed on each leaf disc and left for 48 h for oviposition. After this period the adults were removed. For the egg test, the treatments were sprayed, separately, right after the adults were removed, and after 8 days, the hatched nymphs were counted. For the test with the nymphs, it was waited for 8 days after the removal of the adults and then the treatments were sprayed. Treatment in the adult mite stage resulted in mortality with treatment with Beauveria bassiana, in 89.7% of the individuals, with the chemical product Ortus ® it was observed 90.4% mortality of mites, and with control (water) there was 7.3% mortality of individuals. For the bioassay with the egg stage of the mite it was observed mortality of 93.7% of the individuals treated with Beauveria bassiana, with the chemical product Oberon ® it was found 97.9% mortality of eggs and for the treatment with water was 16.8% of individual mortality. [resumo fornecido pelo autor]
O trabalho teve como objetivo avaliar o uso da Beauveria bassiana no controle do ácaro-rajado. O experimento foi realizado na Universidade de Caxias do Sul. Os tratamentos realizados consistiram em: Água (T1), Ballvéria®(Beauveria bassiana) na dose de 1 kg/ha (T2), Ortus® (princípio ativo: fenpiroximato), na dose de 500 ml/ha e Oberon® (princípio ativo: Espiromesifeno), na dose de 500 mL∙ha-1 (T3). Três discos foliares de morango foram inseridos em placas de Petri, onde já continha papel filtro umedecido. Oito ácaros adultos foram dispostos em cada disco foliar e deixados por 48 h para a oviposição. Após esse período os adultos foram retirados. Para o teste com ovos, os tratamentos foram pulverizados, separadamente, logo após a retirada dos adultos, e após 8 dias, realizou-se a contagem das ninfas eclodidas. Para o teste com as ninfas, aguardou-se por 8 dias após a retirada dos adultos e então realizou-se a pulverização dos tratamentos. O tratamento na fase do ácaro adulto resultou na mortalidade com o tratamento com Beauveria bassiana, de 89,7% dos indivíduos, com o produto químico Ortus ® observou-se 90,4% de mortalidade dos ácaros, e com controle (água) verificou-se 7,3% de mortalidade dos indivíduos. Para o bioensaio com a fase de ovos do ácaro observou-se mortalidade de 93,7% dos indivíduos tratados com Beauveria bassiana com o produto químico Oberon ® constatou-se 97,9% de mortalidade dos ovos e para o tratamento com água foi de 16,8% de mortalidade dos indivíduos. [resumo fornecido pelo autor]
Keywords: Morango - Controle biológico; Pragas - Controle; Ácaro - Controle biológico; Ácaros de plantas